2018
DOI: 10.3201/eid2501.180395
|View full text |Cite
|
Sign up to set email alerts
|

Higher Viral Load of Emerging Norovirus GII.P16-GII.2 than Pandemic GII.4 and Epidemic GII.17, Hong Kong, China

Abstract: We compared viral load of emerging recombinant norovirus GII.P16-GII.2 with those for pandemic GII.Pe-GII.4 and epidemic GII.P17-GII.17 genotypes among inpatients in Hong Kong. Viral load of GII.P16-GII.2 was higher than those for other genotypes in different age groups. GII.P16-GII.2 is as replication competent as the pandemic genotype, explaining its high transmissibility and widespread circulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 15 publications
0
25
0
Order By: Relevance
“…The contribution of the RdRp to the evolutionary rate of caliciviruses became even more clear with the recent success of recombinant GII.2 and GII.4 viruses that acquired a new polymerase variant. For example, the reemerged recombinant norovirus GII.P16-GII.2 that differs from previous GII.P16-GII.2 strains by 5 amino acids in the RdRp (Ruis et al, 2017), results in high virus loads in feces, possesses a relatively high evolutionary rate (5.5 × 10 -3 substitutions/site/year), and has rapidly spread across the world (Ao et al, 2018; Cheung et al, 2019). It has been suggested that the amino acid changes in the new RdRp affect the kinetic properties and the fidelity of the enzyme, but the exact mechanistic details remain unknown.…”
Section: Enzymatic Properties Of Calicivirus Rdrpsmentioning
confidence: 99%
“…The contribution of the RdRp to the evolutionary rate of caliciviruses became even more clear with the recent success of recombinant GII.2 and GII.4 viruses that acquired a new polymerase variant. For example, the reemerged recombinant norovirus GII.P16-GII.2 that differs from previous GII.P16-GII.2 strains by 5 amino acids in the RdRp (Ruis et al, 2017), results in high virus loads in feces, possesses a relatively high evolutionary rate (5.5 × 10 -3 substitutions/site/year), and has rapidly spread across the world (Ao et al, 2018; Cheung et al, 2019). It has been suggested that the amino acid changes in the new RdRp affect the kinetic properties and the fidelity of the enzyme, but the exact mechanistic details remain unknown.…”
Section: Enzymatic Properties Of Calicivirus Rdrpsmentioning
confidence: 99%
“…Additionally, the increase in norovirus activity at the end of 2016 to 2017 may have occurred because of the emergent GII.P16/GII.2 recombinant ( Fu et al, 2017 ; Kwok et al, 2017 ; Liu et al, 2017 ). This GII.P16 genotype presented several amino acid changes in non-structural proteins, such as RdRp, and these changed seemed to facilitate its transmission ( Cannon et al, 2017 ; Tohma et al, 2017 ; Cheung et al, 2019 ). In this study, we analyzed the complete genomes of GII.4 strains collected over 5 years to understand their genetic characteristics and investigate the emergence of GII.P16/GII.4.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the pandemic GII.P16/GII.4 Sydney 2012 norovirus, which does not contain unique substitutions in the capsid, has substitutions within the RdRp that are proposed to increase transmissibility [69]. Infection with this variant also resulted in increased viral shedding compared to other norovirus genotypes, as measured by higher faecal viral loads [70]. Previous studies have shown that RdRp fidelity and intra-host viral diversity affect transmissibility of murine norovirus in vivo , with high-fidelity variants being less efficiently transmitted than the wild-type variant [71].…”
Section: Discussionmentioning
confidence: 99%